A pilot randomized controlled trial of a cognitive‐behavioral therapy guided self‐help mobile app for the post‐acute treatment of anorexia nervosa: A registered report. Issue 3 (7th January 2023) - Fitzsimmons‐Craft, Ellen E.; Laboe, Agatha A.; McGinnis, Claire; Firebaugh, Marie‐Laure; Shah, Jillian; Wallendorf, Michael; Jacobi, Corinna; Bardone‐Cone, Anna M.; Pike, Kathleen M.; Taylor, C. Barr; Wilfley, Denise E.
Abstract: Introduction: Relapse following acute treatment for anorexia nervosa (AN) is common. Evidence suggests cognitive‐behavioral therapy (CBT) may be useful in the post‐acute period, but few patients have access to trained providers. mHealth technologies have potential to increase access to high‐quality care for AN, including in the post‐acute period. The aim of this study is to estimate the preliminary feasibility and effectiveness of a CBT‐based mobile intervention plus treatment as usual (TAU), offered with and without an accompanying social networking feature. Method: In the current pilot randomized controlled trial, women with AN who have been discharged from acute treatment in the past 2 months ( N = 90) will be randomly assigned to a CBT‐based mobile intervention plus treatment as usual (TAU), a CBT‐based mobile intervention including social networking plus TAU, or TAU alone. We will examine feasibility, acceptability, and preliminary effectiveness of the three conditions in terms of reducing eating disorder psychopathology, reducing frequency of eating disorder behaviors, achieving weight maintenance, reducing depression and suicidal ideation, and reducing clinical impairment. We will examine rehospitalization and full recovery rates in an exploratory fashion. We will also examine whether the mobile intervention and social networking feature change the proposed targets and whether changes in targets are associated with benefit, as well as conduct exploratory analyses to identify within‐mobile intervention predictors and moderators of outcome. Discussion: Ultimately, this research may lead to increased access to evidence‐based treatment for individuals with AN and prevention of the extreme negative consequences that can result from this serious disorder. Public Significance: Relapse after acute treatment for anorexia nervosa is common, and few patients have access to trained providers to support them following acute care. This study will pilot a coached mobile app, including a social networking component, for this population. If ultimately successful, our approach could greatly increase access to evidence‐based treatment for individuals with anorexia nervosa and ultimately prevent the extreme negative consequences that can result from this serious disorder.